Knowledge of Extension Professionals regarding Impact of Climate Change in Agriculture - B. S. Ghanghas , P. S. Shehrawat and M. S. Nain, (Indian Journal of Extension Education, 2015)
Empirical study conducted on extension professionals of 19 KVKs under administrative control of CCSHAU Hisarindicated that overall knowledge of extension scientists was found low to moderate which indicate that they were notcompletely abreast of implications of climate change in agriculture. Vast majority had good knowledge in relation toimpact of temperature on crop growth and effect on physio-chemical system of plant. Majority was found well aware ofthe fact that rise in soil temperature increases rate of volatilization and denitrification, affects the soil microbial activitiesand soil temperature affects the soil biomass/organic carbon. Vast majority was found familiar with aspects such as waterpollution affects physio-chemical activities in plant and also creates nutrient deficiency in plant and it leads to suppress thesoil microbial activities. Knowledge of impact of climate change on biodiversity indicated that they had knowledge ofextinction/ near extinction of certain plants/ fruits/trees/animals/birds species and emergence of new insect-pests/diseases whereas only 56.00 percent of them had knowledge that climate change have resulted in suitability for growth ofcertain new crop plants/ fruits/trees/animals/birds species. Necessary efforts should be made to build the capacity of theseextension scientists on impact of climate change especially in harnessing the increased CO level and C- sequestration 2processes and climate resilient species of plants and animal for promotion of remunerativeagriculture.